2006
DOI: 10.1021/bi061213p
|View full text |Cite
|
Sign up to set email alerts
|

ATP Binding Properties of the Soluble Part of the KdpC Subunit from the Escherichia coli K+-Transporting KdpFABC P-Type ATPase

Abstract: P-Type ATPases catalyze the transport of cations across the cell envelope via site-specific hydrolysis of ATP. Modulation of enzyme activity by additional small subunits and/or a second regulatory nucleotide binding site is still a subject of discussion. In the K(+)-transporting KdpFABC complex of Escherichia coli, KdpB resembles the catalytic P-type ATPase subunit, but ATP binding also occurs in the essential but noncatalytic subunit, KdpC. For further characterization, the soluble portion of KdpC (KdpC(sol),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 22 publications
3
27
0
Order By: Relevance
“…However, in strong contrast to KdpC, these so-called FXYD proteins are not essential for enzymatic activity, thereby arguing in favor of the notion that KdpC exhibits a more unique type of regulatory function. Recently, it has been demonstrated that the isolated hydrophilic portion of KdpC (KdpC sol ) specifically binds one ATP molecule at a well-defined binding site, which is in accord with former observations that upon labeling of the KdpFABC complex with the photoreactive ATP analogue 2-azido-ATP, in addition to KdpB also KdpC was labeled significantly (Ahnert et al 2006). This argues in favor of also a regulatory function of KdpC either via interaction with the nucleotide binding pocket of KdpB or via ATP binding itself.…”
Section: The Unique Subunitssupporting
confidence: 82%
See 1 more Smart Citation
“…However, in strong contrast to KdpC, these so-called FXYD proteins are not essential for enzymatic activity, thereby arguing in favor of the notion that KdpC exhibits a more unique type of regulatory function. Recently, it has been demonstrated that the isolated hydrophilic portion of KdpC (KdpC sol ) specifically binds one ATP molecule at a well-defined binding site, which is in accord with former observations that upon labeling of the KdpFABC complex with the photoreactive ATP analogue 2-azido-ATP, in addition to KdpB also KdpC was labeled significantly (Ahnert et al 2006). This argues in favor of also a regulatory function of KdpC either via interaction with the nucleotide binding pocket of KdpB or via ATP binding itself.…”
Section: The Unique Subunitssupporting
confidence: 82%
“…This argues in favor of also a regulatory function of KdpC either via interaction with the nucleotide binding pocket of KdpB or via ATP binding itself. Both the nucleotide affinity and specificity of KdpC was found to be quite low (Ahnert et al 2006), thereby rendering a cooperative regulatory mechanism together with KdpB likely. The site of ATP binding could be located within the conserved C-terminal segment of KdpC.…”
Section: The Unique Subunitsmentioning
confidence: 99%
“…KdpC has a single TM helix at its N-terminus and no known homologs outside of the Kdp system. The 150 residue C-terminal domain of KdpC was shown to bind and be labeled by azido-ATP with relatively low affinity (Ahnert et al, 2006;Altendorf et al, 1992). This observation led to a model in which the large C-terminal domain resided within the cytoplasm and was proposed to help the nucleotide-binding domain of KdpB bind ATP (Bramkamp et al, 2007).…”
Section: Subunit Composition and Topologymentioning
confidence: 99%
“…The middle portion of the protein shows a high variability among all known KdpC polypeptides followed by the C-terminal approximately 70 amino acids, which are highly conserved. This domain is supposed to interact with the N-domain of KdpB and acts as a catalytic chaperone, which guides the ATP into the nucleotide binding pocket (Ahnert et al, 2006;Greie and Altendorf, 2007). An ab initio energy-minimized model of the 90 C-terminal amino acids was generated and fitted into the 3D map in close vicinity to the N-domain of KdpB (Figs.…”
Section: Fitting Of Single Kdpfabc Subunits Into the 3d Mapmentioning
confidence: 99%
“…One possible function is to mediate the structural and functional coupling of KdpA and KdpB, whereby KdpC strongly interacts with KdpA . Recent data on the cytosolic part of KdpC (KdpC sol ) suggest that KdpC might act as a catalytic chaperone, which cooperatively interacts with the nucleotide during catalysis and, thus, increases the rather untypically weak nucleotide binding affinity of the KdpB N-domain (Ahnert et al, 2006). Especially, glutamine 140 of KdpC might play a key role in this process, since it is part of a common ATP binding motif that could interact with the ribose moiety of the ATP molecule, which is inserted into the nucleotide binding pocket of the N-domain .…”
Section: Introductionmentioning
confidence: 99%